Hyperspectral Imaging—A Novel Tool to Assess Tissue Perfusion and Oxygenation in Esophageal Anastomoses - Vaz Pimentel, Duarte; Merten, Larissa; Gosemann, Jan-Hendrik; Gockel, Ines; Jansen-Winkeln, Boris; Mayer, Steffi; Lacher, Martin (European Journal of Pediatric Surgery Reports, 2023)
Anastomotic stricture and leakage are common complications after repair of esophageal atresia (EA). A compromised perfusion of the anastomosis is a contributing factor. Hyperspectral imaging (HSI) is an ultrashort noninvasive method to measure tissue perfusion. We present two cases of with tracheoesophageal fistula (TEF)/EA repair, in whom we applied HSI: the first patient was a newborn with EA type C who underwent open TEF repair. The second one had an EA type A and cervical esophagostomy, in whom we performed gastric transposition. In both patients, HSI confirmed a good tissue perfusion of the later anastomosis. The postoperative course was uneventful and both patients are on full enteral feeds. We conclude that HSI is a safe and noninvasive tool that allows near real-time assessment of tissue perfusion and can contribute to the identification of the optimal anastomotic region during pediatric esophageal surgery.
Keywords: perfusion; hyperspectral imaging; esophageal atresia; anastomotic stricture; anastomotic leakage